Realisasi Pengeluaran Pemerintah Daerah Terhadap Pertumbuhan Ekonomi di Provinsi Sumatera Barat - Yuliarti Yuliarti (Journal of Education on Social Science (JESS), 2020)
To create positive economic growth and maintain economic stability, the role of the government is needed. The implementation of regional autonomy since early 2001 is a form of government strategy to encourage economic growth not only in the regions around the center but also in areas that are far from the center's reach. The implementation of regional autonomy is in accordance with Law No.22 of 1999 concerning regional autonomy, as well as Law No. 32 of 2004 concerning local government. The government can regulate the course of the economy by determining the amount of government revenue and expenditure each year, which is reflected in the National Budget (APBN) for the national budget and the Regional Budget (APBD) for the region or region. This government expenditure is a form of fiscal policy. During the period of 2010-2019, it can be seen that the realization of the expenditure of the government of West Sumatra is more used for indirect expenditure than direct expenditure. For the average economic growth rate over the past ten years, West Sumatra has the second highest average growth rate compared to other provinces, which is 2.24%, but the growth rate per year is still fluctuating and even more often decreases in percentage. Therefore, the authors are interested in examining how the influence of the realization of government spending on economic growth in West Sumatra. The purpose of this study is to find out how much influence the realization of government spending on economic growth in West Sumatra Province. This research uses quantitative data. The data analysis model used is simple linear regression and includes statistical tests. The results of the study show that government spending has a significant effect on economic growth in the province of West Sumatra.